Reviewing Literature and Personal Reflections on Indigenous Land-Based Education - Cormier, Melanie (Scholarship@Western, 2022)
This abstract provides a brief outline of activities occurring during a head and heart fellowship that happened from May 2022 to August 2022 at Western University under the mentorship of Dr. Brent Debassige. During the fellowship, the author initiated a review of academic and grey literatures focusing on Indigenous land-based education occurring on Turtle Island (now known as the Americas). The author, who is an Anishinaabe kwe, also led an Indigenous land-based “re-search” (Absolon and Willett, 2004, p. 7) activity that included personal written reflections on experiences with family. The land-based activity involved foraging for blueberries and Saskatoon berries in northern Ontario. The preliminary findings from this fellowship will inform a master’s research project to be completed by the end of April 2023. During personal reflective writing, I (the author) was reminded of how the relationship Indigenous people have with the land is reciprocal, and how the Anishinaabe have relied on traditional harvesting practices since time immemorial. As an integrated component of the reflective writing, I started a review of literature on land-based education. I used Diana Ridley’s (2012) textbook, The Literature Review: A step-by-step guide for students, to inform the approach for my systematic search of the relevant literature. I made modifications to Ridley’s approach to include land-based reflections, and I searched for associations between my personal experiences and findings from the scholarly literature. One preliminary finding from this re-search project involves uncovering a gap in research studies concerning Anishinaabe personal reflections on traditional berry harvesting practices. Implications for future research could investigate the educational outcomes derived from sustainable land-based practices for learners of all ages. The outcomes from this study are significant as all human and other-than-human beings face a global ecological crisis that requires a shift in how humans co-exist with mother earth.